A Critical Review on the Book Plato: Deconstruction of a Philosophical Myth - Hassan Fathi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this book Plato: Deconstruction of a Philosophical Myth, Shervin Vakili tries to show that the portrait of Plato drawn by the so-called scholars of Plato (both western and Iranian) is verily unreal. In nine sections of this book, Vakili completes a portrait of Plato which lacks ethical and Political vices; a person who learned everything from Persians and turned everywhere against them. Vakili’s Plato is a stony aristocrat, an ambitious treacherous, and deviator of the Persian theoretical and practical teachings. Vakili introduces very historical pieces of evidence from Greek-Persian relations to validate his portrait, but after reading his book, it is not hard to say that he lacks a comprehensive, original, and deep understanding of Plato’s teachings. Most of his comments and analyses are unscholarly, and some are notoriously mistaken. Some critical points have been said here, about this amassed book.